Emotional problems in mothers of autistic children and their correlation with socioeconomic status and the children's core symptoms. Issue 32 (August 2019) - Zhou, Wensu; Liu, Dan; Xiong, Xiyue; Xu, Huilan
Abstract : Abstract: To investigate the emotional problems (depressive and anxiety symptoms) of mothers of children with autism spectrum disorder (ASD) and explore the role of the mother's socioeconomic status (SES) and the core symptoms of the child on the mother's emotional problems. This cross-sectional survey was performed in 180 mothers of children with ASD in Chang Sha city of China. The 7-item Generalized Anxiety Disorder Scale (GAD-7) and the 9-item Patient Health Questionnaire (PHQ-9) were used to assess the anxiety and depressive symptoms of the mothers of the autistic children. The education level and annual family income, as well as occupation, were be selected as components of the mother's SES. Autism Behaviour Checklist (ABC) and Social Responsiveness Scale (SRS) were used for the evaluation of the core symptoms of the children. A general information questionnaire was also used. The ordinal regression was used to examine the effect of the SES and children's core symptoms on maternal emotional problems. The valid response rate was 92.7% (167 of 180 questionnaires were returned). Of the mothers studied, 72.5% and 80.2% had depressive and anxiety symptoms, respectively, and 67.1% suffered from both symptoms. Mother's SES was observed to be unrelated to maternal anxiety symptoms ( P  >.05). Only 1 component of the SES (junior high school education level) was related to depressive symptoms (OR = 0.31, 95% CI 0.12–0.80). SRS score under 115 (OR = 0.38, 95% CI 0.16–0.93) of autistic children was a protective factor against maternal anxiety symptoms. The borderline and mild behavioral problems (OR = 0.43, 95% CI 0.19–0.99; OR = 0.45, 95% CI 0.22–0.94, respectively) of autistic children were protective factors against maternal depressive symptoms. Mothers of autistic children generally exhibited high levels of anxiety and depressive symptoms. The core symptoms of the autistic children were observed to be strongly associated with both maternal anxiety and depressive symptoms. Improvements in the core symptoms of children with ASD may help reduce maternal anxiety and depressive symptoms to some extent.